Doping of thermoelectric PbSe with chemically inert secondary phase nanoparticles. Issue 41 (16th October 2017) - Wu, Chao-Feng; Wang, Heng; Yan, Qimin; Wei, Tian-Ran; Li, Jing-Feng
Abstract : Chemically inert nanoparticles were composited with semiconducting PbSe, realizing co-optimization on both mechanical strength and thermoelectric performance with a new doping mechanism related to interfaces. Abstract : For thermoelectrics, as well as many other applications of semiconductors, optimizing the carrier density is of great importance. This is normally done by atomic substitution. In this study, we present a result where systematic doping could arise from the least expected nanoparticles when composites are formed. We achieved this in a composite of PbSe and nanoparticle SiC. High carrier concentrations of up to 2 × 10 19 cm −3 were achieved with SiC nanoparticle load up to 5 vol%. We believe this is due to interfaces that stabilized more defects than is allowed in bulk PbSe. Eventually, the nanoparticle-induced doping effect led to a decent thermoelectric performance with zT close to one at 800 K, comparable to optimized PbSe using conventional dopants. Our result indicates the good potential of this uncommon mechanism in some semiconductors for carrier concentration tuning where conventional doping has been found difficult.